Evaluasi Atas Pengakuan Pendapatan dan Beban Pada Perusahaan Jasa Konstruksi Dalam Kaitannya Terhadap Laporan Laba Rugi Perusahaan. Studi Kasus pada PT. Tunas Mekar Eka Harpedi - Nuruzzaman, Muhammad; Setiady, Agus (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2009)
The purpose of this research is to evaluate income and burden acknowledgement at construction service company carrying out contraction work contract with Pemerinyah Kabupaten Bogor â Dinas Cipta Karya as work giver. The evaluation is done to find out how income and burden acknowledgement by the company in correlation with loss and profit reporting of the company will be. The result of the research shows that PT Tunas Mekar Eka Harpedi has given positive grade concerning income and burden acknowledgement. The accuracy of income and cost value presented at loss profit report is in accordance with work contract value that was carried out by the company. Whereas the evaliation result done by researcher at PT Tunas Mekar Eka Harpedi shows that the income of contruction service company is in the shape of project income. That income has been acknowledged by the company by accural basis method and settlement percentage method. Itâs toward burden acknowledgement as well. Accounting policy which has been estableshed to loss and profit report by PT Tunas Mekar Eka Harpedi is in accordance with PSAK No. 1 about Finance Reporting and matches accounting experâs opinion quoted at chapter II. Accurate comparison between income and burden can fulfil quantitative characteristic of finance reporting and it has influence towards loss and profit reporting. Keywords : Income and burden acknowledgement; Loss and profit report